Does pattern bargaining explain wage restraint in the German public sector? - Donato Di Carlo (Max Planck Institute for the Study of Societies, 2018)
German public sector wage restraint has been explained through the presence of a specific type of inter-sectoral wage coordination in the industrial relations system - i.e., export sector-led pattern bargaining. This paper has a twofold ambition. First, as a literature-assessing exercise, I review the literature in industrial relations and comparative political economy (CPE) and find that (1) the origins and mechanics of inter-sectoral wage coordination through pattern bargaining have never been laid out clearly; (2) the mechanisms of the pattern bargaining thesis have never been tested empirically; and (3) the CPE literature reveals a limiting export-sector bias. Second, as a theory-testing exercise, I perform hoop tests to verify whether the pattern bargaining hypothesis can really account for wage restraint in the German public sector. I find that Germany cannot be considered a case of export sector-driven pattern bargaining. These findings challenge core tenets of a longstanding scholarship in both CPE and industrial relations. Most importantly, they open a new research agenda for the study of public sector wage-setting that should shift its focus to public sector employment relations, public finance, public administrations, and the politics of fiscal policy. – – Die Lohnzurückhaltung im deutschen öffentlichen Sektor wird typischerweise mit der Präsenz eines spezifischen Typs der intersektoralen Lohnkoordination erklärt, und zwar des export sector-led pattern bargaining. Vor diesem Hintergrund verfolgt das Papier zwei Ziele. Erstens wird die Literatur zum Thema aufgearbeitet. Dabei zeigt sich: (1) Über die Ursprünge und Mechanismen dieses Lohnaushandlungsmodells besteht wenig Klarheit; (2) soweit Mechanismen spezifiziert wurden, wurden sie nicht empirisch überprüft; (3) bisher hat die Vergleichende Politische Ökonomie den Exportsektor mehr als den Binnensektor untersucht. Zweitens wird getestet, ob die Lohnzurückhaltung im deutschen öffentlichen Sektor wirklich mit dem Modell zu erklären ist. Wie sich zeigt, lässt sich Deutschland nicht als Beispiel für exportdominierte intersektorale Lohnkoordination anführen. Diese Erkenntnisse stellen Annahmen der Literatur über Arbeitsbeziehungen und der Vergleichenden Politischen Ökonomie infrage. Zudem öffnen sie eine neue Forschungsagenda zum Thema Lohnaushandlung im öffentlichen Sektor. Statt auf vermeintliche intersektorale Lohnkoordination müsste sich diese Forschungsagenda auf die spezifische Struktur der Arbeitsbeziehungen im öffentlichen Sektor, auf die öffentlichen Finanzen, die öffentliche Verwaltung und die Fiskalpolitik konzentrieren.
hdl:21.11116/0000-0001-2DBF-7
Keywords: 300; pattern bargaining; public sector; collective bargaining; wage coordination; hoop tests; Germany; Tarifvertrag; Öffentlicher Dienst; Pilotabschlüsse; Lohnpolitik; Arbeitsbeziehungen